'Two feet' as citizenship strategy: an anthropological perspective on instrumental approaches to citizenship among people of Indian origin in Tanzania. Issue 3 (2nd September 2017) - Schou Pallesen, Cecil Marie
ABSTRACT: With point of departure in the emic concept of 'two feet, ' the article explores how transnationalism by 'keeping a foot in the door' is being practiced among people of Indian origin living in Tanzania. Indians settled in East Africa in the late nineteenth century and since the end of colonial rule they have been aware of distributing different citizenships within the families in order to stay transnationally mobile after independence. Numerous Indians moved to the U.K. and Canada in the years following independence and those who stayed back made sure to 'keep the door open' and thus secure a potential future abroad. 'Two feet, ' the article argues, is a practice that ensures a necessary level of social protection for the East African Indians. Shedding light on ways in which lifeworlds stretched across national borders unfold on a micro level, the article shows how 'two feet' is a gendered practice in which women's purity becomes intertwined with transnational mobility and the potentiality of different places.